Information on Flower Coloration and Pigmentation in Current Carnation Cultivars for Use in Future Flower-color Breeding - Morimoto, Hayato; Ando, Yuka; Sugihara, Hiroaki; Narumi-Kawasaki, Takako; Takamura, Takejiro; Fukai, Seiichi (Horticulture journal, 2021)
Current carnation cultivars have a wide range of flower colors, which is one of the important traits for the flower market. Since large numbers of commercial carnation cultivars bearing various flower colors and flower color patterns have been developed over the last few decades, a comprehensive understanding of the diversity of flower color characteristics has become difficult to achieve. In this study, 56 standard carnation cultivars and 54 spray carnation cultivars were collected and evaluated in terms of flower color and flower color pattern, two visual traits, and flower pigments. Visual flower color analysis indicated that the flower color pattern of the 110 cultivars could be categorized into five typical types and two minor types, and the five typical types were further classified into 16 sub-types. Additionally, flower colors of these carnations could be categorized into 15 hues. High-performance liquid chromatography (HPLC) analysis indicated that carnation flower color is basically determined by the combination of pelargonidin and cyanidin-based anthocyanins, chalcononaringenin 2'-O-glucoside and chlorophyll, giving cyanic, yellow and green color, respectively. Microscopic observation of the petal epidermis indicated that formation of anthocyanin aggregates in the vacuoles and cell shape affect color perceptions, either metallic or velvety, and this is involved in flower color diversification. A fundamental investigation of flower color characteristics will support further developments in flower-color breeding.